2020
DOI: 10.3389/fpsyg.2020.00971
|View full text |Cite
|
Sign up to set email alerts
|

The Other-Race-Effect on Audiovisual Speech Integration in Infants: A NIRS Study

Abstract: Previous studies have revealed perceptual narrowing for the own-race-face in face discrimination, but this phenomenon is poorly understood in face and voice integration. We focused on infants' brain responses to the McGurk effect to examine whether the other-race effect occurs in the activation patterns. In Experiment 1, we conducted fNIRS measurements to find the presence of a mapping of the McGurk effect in Japanese 8to 9-month-old infants and to examine the difference between the activation patterns in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 50 publications
7
13
0
Order By: Relevance
“…The ratio of "fused" perception for audiovisual incongruent stimuli (/ta/ perception for the /pa/ sound and /ka/ video) was higher for the own-race face. Our results provide supportive evidence for the other-race effect within the McGurk effect (Ujiie et al, 2020). A previous study showed that 8-to 9-month-old infants can perceive the McGurk effect in the case of an own-race speaker, but not in the case of an other-race speaker (Ujiie et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The ratio of "fused" perception for audiovisual incongruent stimuli (/ta/ perception for the /pa/ sound and /ka/ video) was higher for the own-race face. Our results provide supportive evidence for the other-race effect within the McGurk effect (Ujiie et al, 2020). A previous study showed that 8-to 9-month-old infants can perceive the McGurk effect in the case of an own-race speaker, but not in the case of an other-race speaker (Ujiie et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Our results provide supportive evidence for the other-race effect within the McGurk effect (Ujiie et al, 2020). A previous study showed that 8- to 9-month-old infants can perceive the McGurk effect in the case of an own-race speaker, but not in the case of an other-race speaker (Ujiie et al, 2020). If the previous results reflect the same other-race effect as in facial perception (e.g., Kelly et al, 2007, 2009), it can be assumed that this effect would also be observed in adults.…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations